A Newly Developed Aerosol Exposure Apparatus for Heated Tobacco Products for In Vivo Experiments Can Deliver Both Particles and Gas Phase With High Recovery and Depicts the Time-Dependent Variation in Nicotine Metabolites in Mouse Urine. Issue 12 (10th June 2021) - Sawa, Marie; Ushiyama, Akira; Inaba, Yohei; Uchiyama, Shigehisa; Hattori, Kenji; Ogasawara, Yuki; Ishii, Kazuyuki
Abstract: Introduction: There is no standardized aerosol exposure apparatus to deliver heated tobacco products (HTPs) for in vivo experiments. Therefore, we developed a novel HTPs aerosol exposure apparatus for mice and demonstrated that nicotine and other chemicals in HTPs aerosol generated by the apparatus can be delivered to mice which replicate human smoke. Aims and Methods: The amounts of nicotine, tar, and carbon monoxide (CO) in IQOS (Marlboro Regular HeatSticks) aerosol generated by two types of apparatuses were determined. C57BL/6N mice were exposed to IQOS aerosol, followed by determination of the urinary nicotine metabolites. Further, the skin surface temperature of mice was monitored to confirm the vasoconstriction action of nicotine. Results: The amount of chemicals in IQOS aerosol by the novel air push-in inhalation apparatus for HTPs (APIA) was equivalent to that of the analytical vaping machine (LM4E) (1.60 ± 0.08 [APIA] vs. 1.46 ± 0.07 mg/stick [LM4E] in nicotine and 0.55 ± 0.04 [APIA] vs. 0.45 ± 0.01 mg/stick [LM4E] in CO). After mice were exposed to IQOS aerosol by APIA, the urinary nicotine metabolite levels were determined; peak values in cotinine and 3-hydroxycotinine (3-HC) were 6.82 μg/mg creatinine at 1 hour after exposure and 32.9 μg/mg creatinine at 2 hours after exposure, respectively. The skin surface temperature decreased and was lower (33.5°C ± 0.5°C) at 30 minutes than before exposure (37.6°C ± 0.8°C). Conclusions: The new apparatus for HTPs aerosol exposure to mice showed good performances in terms of both chemical analysis of collected aerosol and fluctuations in the urinary nicotine metabolites. Implications: The APIA reported in this study can expose small animals to HTPs aerosol, including nicotine and other chemical substances as same amounts as LM4E and replicate actual human smoking process by in vivo experiments. Therefore, the experiments using APIA can provide evidence to assess the health risks of HTPs use.